Molecular Engineering of Porphyrins as Organocatalysts and Methods Development for New Highly Substituted Porphyrins - KIELMANN, MARC (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2019)
Chapter 1 introduces the N–H…X binding motif in tetrapyrroles, which forms the basis of the research carried out on organocatalytically active porphyrins in Chapters 3.1–3.3. Specifically, the role of porphyrin(oid) ligands in various coordination-type complexes, means to access the core for hydrogen bonding, and the concept of conformational control are discussed. As will be shown, a good understanding of these aspects is vital to promote emerging applications for porphyrins, such as organocatalysis and sensors. Chapters 3.1 and 3.2 focus on the synthesis of potential nonplanar porphyrin organocatalysts and their application in Michael additions and Henry reactions. This was propelled by the idea that the bifunctional core of tetrapyrroles should be accessible for intermolecular interactions upon sufficient distortion of the macrocycles. An underlying principle is that in planar porphyrins, the inner core system, which has basic imine and acidic amine groups, is buried within the macrocycle plane. As a result, a molecular engineering approach was perused in order to reshape the vector of N/N–H orientation outwards and allow these functional groups to activate appropriate small molecules. This was successfully transformed into a first case study where highly substituted porphyrins, such as 2,3,7,8,12,13,17,18-octaethyl-5,10,15,20-tetraphenylporphyrin (H2OETPP, 74) acted as efficient organocatalysts. In Chapter 3.3, a series of 5,10,15,20-tetraphenylporphyrins with graded degrees of β-ethyl substitution was applied in sulfa-Michael test reactions to correlate the degree of nonplanarity with their catalytic activity. The aim was to provide a better understanding and additional proof for the likely bifunctional mode of activation, accompanied by density functional theory (DFT) calculations. Chapters 3.4 and 3.5 focus on methods development to produce new highly substituted porphyrins with tailored properties. First, in Chapter 3.4, a series of porphyrin thioethers was synthesized from 2,3,7,8,12,13,17,18-octaethyl-5,10,15,20-tetranitroporphyrin (H2OETNP, 95) in straightforward substitution reactions followed by their thorough structural evaluation in the solid state. At the same time, a new IV methodology for the stepwise denitration of 95 was elaborated and accompanied by single crystal X-ray structural analyses of all 2,3,7,8,12,13,17,18-octaethylporphyrins with 1–4 meso-nitro groups. Therein, the goal was to to deduce interrelationships between substituent pattern, specific conformations, and potential for new applications. Next, in Chapter 3.5, it was attempted to introduce a new general-purpose method for preparing regioisomerically pure, highly substituted type I porphyrins based on steric considerations. Through rational choice of easily accessible aldehyde and pyrrole components with tailored steric bulk, it was possible to synthesize several type I porphyrins that were not contaminated by other type isomers. This is important because porphyrin type isomers have synthetic and biological relevance. Therefore, a reliable route to access a broad range of such compounds is an important step towards the design and engineering of systems for biomedical studies.
APPROVED
Keywords: Organocatalysis; Porphyrins; Molecular Engineering; Methods Development; Nucleophilic Aromatic Substitution; Type I Porphyrins; Nonplanar Porphyrins; Highly Substituted Porphyrins; Tetrapyrroles